The Role of the Pediatric Pharmacist in Personalized Medicine and Clinical Pharmacogenomics for Children: Pediatric Pharmacogenomics Working Group - Kennedy, Mary Jayne (Pediatric Pharmacy Advocacy Group, 2011)
With the initiatives by the National Institutes of Health and the Food and Drug Administration, pharmacogenomics has now moved from the laboratory to the patient bedside. Over 100 drug-products now contain pharmacogenomic information as part of their labeling. Many of these are commonly used in the pediatric population. Direct-to-consumer genetic test kits also require intervention and guidance from healthcare professionals. This increased trend towards personalized medicine mandates that healthcare professionals develop a working knowledge about pharmacogenomics and its application towards patient care. Because pharmacogenomic testing can provide patient-specific predictors for response to and safety of medications, pharmacists are positioned to play an active role in pharmacogenomic testing, clinical interpretation of results, and recommendations for individualization of drug therapy. Opportunities for pharmacists exist in both inpatient and outpatient settings, such as pharmacist-managed clinical pharmacogenomics consultation services and educating patients and families about pharmacogenomic testing. In addition to clinical roles, pharmacists may also be involved in genetically-influenced drug discovery and development. Given the potential for genetic and age-dependent factors to influence drug selection and dosing, pediatric pharmacists should be involved in the development of dosing recommendations and interprofessional practice guidelines regarding pharmacogenomic testing in pediatric patients. Opportunities to become knowledgeable and competent in pharmacogenomics span from coursework as part of the pharmacy curriculum to postgraduate education (e.g., residencies, fellowships, continuing education). However, there exists a need for additional postgraduate learning opportunities for practicing pharmacists. As a result, the Pediatric Pharmacy Advocacy Group (PPAG) acknowledges a need for increased education of both student and practicing pharmacists, with consideration of special patient populations, such as infants and children. PPAG endorses and advocates for the involvement of pediatric pharmacists in pharmacogenomic testing and in using those results to provide safe and effective medication use in pediatric patients of all ages. Additionally, PPAG strongly encourages pediatric pharmacists to take responsibility for educating patients and their families about the importance of pharmacogenomic testing and its role in the safe and effective use of medications.